ChemInform Abstract: 4‐Oxothiazolidines with Exocyclic C=C Double Bond(s): Synthesis, Structure, Reactions and Biological Activity. Issue 2 (January 2015) - Stojanovic, Milovan; Dzambaski, Zdravko; Bondzic, Bojan; Aleksic, Jovana; Baranac‐Stojanovic, Marija
Abstract Review: 183 refs.